2022
DOI: 10.3390/tomography8020064
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sealer Application Methods on Voids Volume after Aging of Three Calcium Silicate-Based Sealers: A Micro-Computed Tomography Study

Abstract: During obturation, air voids are undesirable as they may provide shelter for microorganisms or passage for fluids. This study aimed to compare the occurrence of voids between three calcium silicate-based sealers (CSBSs) (MTA-Fillapex, BioRoot-RCS, Bio-C) and the change in their volume after aging. In addition, we aimed to compare voids when using two sealer application methods: lentulo-spiral (LS) and gutta-percha (GP) cone. Thirty extracted mandibular premolars (n = 30) were endodontically prepared and obtura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
2
12
0
2
Order By: Relevance
“…However, in the present study, gap‐free interfacial adaptations were not observed. This data agrees with previous studies that use these same materials for retro‐filling and perforation sealing (Atmeh et al, 2022; Bianco et al, 2020; Jardine et al, 2021). However, the fact that they have good properties (alkalinization, induction of mineralized tissue, and good sealing) to use in cases of perforation or root filling could also be profitable for use in cases of surgical retreatment.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the present study, gap‐free interfacial adaptations were not observed. This data agrees with previous studies that use these same materials for retro‐filling and perforation sealing (Atmeh et al, 2022; Bianco et al, 2020; Jardine et al, 2021). However, the fact that they have good properties (alkalinization, induction of mineralized tissue, and good sealing) to use in cases of perforation or root filling could also be profitable for use in cases of surgical retreatment.…”
Section: Discussionsupporting
confidence: 92%
“…These results for Total Fill BC Sealer and BioRoot RCS are in agreement with previous studies [ 9 ]. However, a statistically significant increase in total volume of pores after 8 weeks of storage in a phosphate-rich medium for BioRoot RCS was observed by Atmeh et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pores was most frequently analyzed due to the space in which bacteria can re-grow and proliferate, causing long-term treatment failures [ 9 , 26 , 28 , 31 , 44 , 45 ]. Unfortunately, none of the filling materials or application methods can provide a pore-free root canal filling [ 9 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations